INTRODUCING A LOCAL PRODUCT OF INDONESIA (SOFA FROM USED DRUM) TO EUROPEAN MARKET - Ahmad Arif Al Rizky; Muhammad Zainul Hakim; Jeroen Bobeldijk; Trixi Winata (AIBPM Publisher, 2017)
International Marketing is a kind of activity business which can improve relationship between each country. Besides, international marketing also useful to fulfill of needed in each country by exporting or importing typical goods from each country and expand the market for Indonesia. CV Cahaya Mustika is a company which is trying to export a local product from Indonesia which is a Sofa made from used drum. According to company condition right now, CV Cahaya Mustika isn’t readiness to enter the international marketing because of the financial burden. So, with Nusantara Project that give a solution and idea for joining the international marketing, CV Cahaya Mustika have a potential to joining the International Marketing. Nusantara Project also selection a country that which country have a high demand of goods sold from Company based on the data and Nusantara project gave an information of which fright forwarder that have a low prices and high trust for exporting goods. So, with the condition of company, as Nusantara Project should gave a solution to joining the company into international Marketing for improving quality of the company also expand the market of Indonesia.